Methods of the International Tobacco Control (ITC) EUREST-PLUS ITC Europe Surveys. (12th September 2020) - Thompson, Mary E; Driezen, Pete; Boudreau, Christian; Bécuwe, Nicolas; Agar, Thomas K; Quah, Anne C K; Zatoński, Witold; Przewoźniak, Krzysztof; Mons, Ute; Demjén, Tibor; Tountas, Yannis; Trofor, Antigona; et al.
Abstract: Background: The EUREST-PLUS ITC Europe surveys aim to evaluate the impact of the European Union's Tobacco Products Directive (EU TPD) implementation within the context of the WHO FCTC. This article describes the methodology of the 2016 (Wave 1) and 2018 (Wave 2) International Tobacco Control 6 European (6E) Country Survey in Germany, Greece, Hungary, Poland, Romania and Spain; the England arm of the 2016 (Wave 1) and 2018 (Wave 2) ITC 4 Country Smoking and Vaping (4CV) Survey; and the 2016 (Wave 10) and 2017 (Wave 11) ITC Netherlands (NL) Survey. All three ITC surveys covering a total of eight countries are prospective cohort studies with nationally representative samples of smokers. Methods: In the three surveys across the eight countries, the recruited respondents were cigarette smokers who smoked at least monthly, and were aged 18 and older. At each survey wave, eligible cohort members from the previous waves were retained, regardless of smoking status, and dropouts were replaced by a replenishment sample. Results: Retention rates between the two waves of the ITC 6E Survey by country were 70.5% for Germany, 41.3% for Greece, 35.7% for Hungary, 45.6% for Poland, 54.4% for Romania and 71.3% for Spain. The retention rate for England between ITC 4CV1 and ITC 4CV2 was 39.1%; the retention rates for the ITC Netherlands Survey were 76.6% at Wave 10 (2016) and 80.9% at Wave 11 (2017). Conclusion: The ITC sampling design and data collection methods in these three ITC surveys allow analyses to examine prospectively the impact of policy environment changes on the use of cigarettes and other tobacco products in each country, to make comparisons across the eight countries.